"Be Kind But Not Too Kind": Black Males' Prosocial Behaviors in the Face of Dehumanization. (5th April 2022) - Harris, Johari; Kruger, Ann Cale
Abstract : This qualitative study examined how adolescent Black males ( N  = 12) talk about their identities, prosocial behaviors, and connections between them. Of special interest was whether and how the participants included their experiences of dehumanization. Focus group data were analyzed using modified analytic induction. Participants felt good about their racially gendered identities but felt they occupied a precarious position in the United States. Participants' beliefs about how others viewed them motivated restraint from engaging in too many prosocial acts to prevent appearing vulnerable. Participants explicitly referred to their experience of oppression in these discussions and its interaction with identity and prosociality. Results suggest research must consider how macro‐level processes like racism influence the identities and prosocial behaviors of adolescent Black males.